The Neuropathology of Older Persons with and Without Dementia from Community versus Clinic Cohorts - Schneider, Julie A. (2009)
Community-based cohorts of older persons may differ neuropathologically from clinic-based cohorts. This study investigated age-related pathologies in persons with and without dementia and included autopsied participants from two community-based cohorts, the Rush Religious Orders Study (n = 386) and the Memory and Aging Project (n = 195), and one clinic-based cohort, the Clinical Core of the Rush Alzheimer’s Disease Center (n = 392). Final clinical diagnoses included no cognitive impairment (n = 202), mild cognitive impairment (MCI) (n = 150), probable Alzheimer’s disease (AD) (n = 474), possible AD (n = 88), and other dementias (n = 59). Postmortem diagnoses included pathologic AD, cerebral infarcts, and Lewy body disease. Community-based persons with clinical AD had less severe AD pathology (p < 0.001) and had more cerebral infarcts (p < 0.001) compared to clinic-based persons. Additionally, community-based persons with MCI had more infarcts compared to clinic-based persons. Overall, there was a higher proportion of Lewy bodies and atypical pathologies in the clinic-based compared to the community-based cohorts (p < 0.001). Community-based persons with probable AD show less severe AD pathology and more often have infarcts and mixed pathologies; those with MCI more often have infarcts and mixed pathologies. Overall, clinic-based persons have more Lewy bodies and atypical pathologies. The spectrum of pathologies underlying cognitive impairment in clinic-based cohorts differs from community-based cohorts.